1993
DOI: 10.1002/syn.890150407
|View full text |Cite
|
Sign up to set email alerts
|

Development of dopamine‐beta hydroxylase—positive fiber innervation of the rat hippocampus

Abstract: Development of the noradrenergic fiber innervation of the rat hippocampus by the locus coeruleus was examined immunohistochemically in fixed tissue from animals aged 4 days through 55 days postnatal. The presence of tyrosine hydroxylase (TH) and dopamine-beta-hydroxylase (DBH) immunoreactive cells and fibers was evaluated in sections of hippocampus and locus coeruleus. Large, multipolar TH- and DBH-positive cells with long beaded fibers were visible within locus coeruleus at all ages; no immunopositive cell bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…Furthermore, noradrenaline induces secretion of IL-6 by astrocytes (Maimone et al, 1993), as IL-6 is responsible (via a NOX-dependent superoxide overproduction) of PV impairment in ketamine-treated and aged rodents Dugan et al, 2009). Interestingly, noradrenergic innervations in VH are especially dense in CA3 and hilus of the DG (Oleskevich et al, 1989) and reach maximum density after weaning age (Moudy et al, 1993), coinciding in time and location with the oxidative stress observed in GCLM Ϫ/Ϫ mice. Thus, a compromised GSH system might not cope with high levels of noradrenaline release in the ventral CA3 and DG, causing a regional oxidative stress.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, noradrenaline induces secretion of IL-6 by astrocytes (Maimone et al, 1993), as IL-6 is responsible (via a NOX-dependent superoxide overproduction) of PV impairment in ketamine-treated and aged rodents Dugan et al, 2009). Interestingly, noradrenergic innervations in VH are especially dense in CA3 and hilus of the DG (Oleskevich et al, 1989) and reach maximum density after weaning age (Moudy et al, 1993), coinciding in time and location with the oxidative stress observed in GCLM Ϫ/Ϫ mice. Thus, a compromised GSH system might not cope with high levels of noradrenaline release in the ventral CA3 and DG, causing a regional oxidative stress.…”
Section: Discussionmentioning
confidence: 87%
“…In the hippocampal formation, noradrenergic innervation is particularly dense in areas receiving mossy fiber input, i.e., in the hilus of the dentate gyrus and in stratum lucidum of the CA3 subfield. Stratum lacunosum-moleculare of the CA1 region is also heavily innervated, but other regions and layers receive relatively sparse input (Loy et Moudy et al, 1993).…”
Section: V4 Noradrenergic Innervation Of the Hippocampal Formationmentioning
confidence: 99%
“…However, DA levels in the hippocampus do not just depend on dopaminergic innervations, as lesions in, for example, hippocampal noradrenergic neurons significantly reduce DA levels (Bischoff et al 1979). Moreover, locus coeruleus (LC) fibers densely innervate the hippocampal formation including the stratum radiatum (Moudy et al 1993) and enable a direct release of DA from noradrenergic LC fibers in the CA1 region (Smith and Greene 2012). It is thus possible that DA might be released from noradrenergic fiber terminals to “compensate” for the limited, or absent, VTA-mediated release of DA to the stratum radiatum and other dorsal hippocampal subregions, thus enabling DA to regulate synaptic plasticity and learning processes that are mediated by dorsal hippocampal structures.…”
Section: What Enables the Differences In D1/d5 Regulation Of Hippocammentioning
confidence: 99%